Predictive coding and religious belief - Van Eyghen, Hans (Filosofia Unisinos, 2018)
In this paper I investigate the epistemic implications of a recent theory of religious cognition that draws on predictive coding. The theory argues that certain experiences are heavily shaped by a subject’s prior (religious) beliefs and thereby makes religious believers prone to detect invisible agents. The theory is an update of older theories of religious cognition but departs from them in crucial ways. I will assess the epistemic implications by reformulating existing arguments based on other (older) theories of religious cognition.